ANFIS Based Control Design for AGC of a Hydro-hydro Power System with UPFC and Hydrogen Electrolyzer Units. Issue 4 (25th February 2018) - Sharma, Gulshan; Nasiruddin, Ibraheem; Niazi, Khaleequr Rehman; Bansal, Ramesh C.
Abstract: This paper presents the design of artificial neuro fuzzy inference system (ANFIS) based automatic generation control (AGC) scheme for a two-area hydro-hydro dominating power system. The proposed control scheme is flexible with simple structure and may prove to be a promising tool for considered system in the presence of system non-linearity and for wide range of parametric variations. The ANFIS based control are implemented and the system dynamic responses are obtained considering 1% load disturbance in area-1 and compared with fuzzy and conventional proportional integral (PI) based AGC to show the simplicity and effectiveness of the proposed control. The further improvements in the system dynamic responses with the proposed control are observed by considering the unified power flow control (UPFC) in series with the tie-line and hydrogen aqua electrolyzer units installed at one of the terminal of the control areas. The dynamic performance of the designed control is also evaluated considering the governor dead-band and generation rate constraint (GRC) non-linearity and for wide range of system parametric variations.